The status of intercultural mediation in translation: Is it an absolute licence? - Akbari Alireza; Darani Parviz Ahmadi (Topics in Linguistics, 2017)
The role of translator as Sprachmittler or intercultural mediator has welcomed much attention since the advent of the “cultural turn” paradigm. The present research paper seeks to figure out how the manifestations of intercultural mediation are achieved via translation in terms of two mediation facets, viz, personal and communicated interpretations. Whereas the former deals with the presence of the translator between the source and target cultures, the latter concerns the role of the reader of the translated text in the target language through several mediational strategies including: expansion, reframing, replacement, eschewing of dispreferred structure, and dispensation to capture the message of the source text. The rationale for focusing on these strategies lies in the fact that translators often utilize transliteration and literal translation strategies when it comes to cultural items and concepts. As far as review of the literature indicates, mediational translation has not received due attention in the Persian language since it differs in comparison with other languages such as English, French etc. In the case of language patterning, such study reveals some novel but applicable cultural translation strategies that highlight the nature of mediation in cultural translation.